2018
DOI: 10.1002/anie.201710557
|View full text |Cite
|
Sign up to set email alerts
|

Van der Waals Heterostructures Comprised of Ultrathin Polymer Nanosheets for Efficient Z‐Scheme Overall Water Splitting

Abstract: Inspired by natural photosynthesis, Z-scheme photocatalytic systems are very appealing for achieving efficient overall water splitting. Developing metal-free Z-scheme photocatalysts for overall water splitting, however, still remains challenging. The construction of polymer-based van der Waals heterostructures as metal-free Z-scheme photocatalytic systems for overall water splitting is described using aza-fused microporous polymers (CMP) and C N ultrathin nanosheets as O - and H -evolving catalysts, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
169
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(174 citation statements)
references
References 38 publications
3
169
0
2
Order By: Relevance
“…Theresults exhibited that CTF-HUST-A1 samples with suitable energy levels constitute theoretical potentials for photocatalytic overall water splitting. [7] Thep orous structures of the samples are studied by nitrogen adsorption-desorption isotherm measurements (Supporting Information, Figure S30). According to the nitrogen sorption isotherm curves (Supporting Information, Figure S30a), the Brunauer-Emmett-Teller (BET) surface areas of CTF-HUST-A1-K 2 CO 3 is only calculated to be 156 m 2 g À1 .T he BET surface areas of CTF-HUST-A1-KOH, CTF-HUST-A1-EtOK, and CTF-HUST-A1-t BuOK are gradually increased to 210 m 2 g À1 ,4 12 m 2 g À1 ,a nd 644 m 2 g À1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theresults exhibited that CTF-HUST-A1 samples with suitable energy levels constitute theoretical potentials for photocatalytic overall water splitting. [7] Thep orous structures of the samples are studied by nitrogen adsorption-desorption isotherm measurements (Supporting Information, Figure S30). According to the nitrogen sorption isotherm curves (Supporting Information, Figure S30a), the Brunauer-Emmett-Teller (BET) surface areas of CTF-HUST-A1-K 2 CO 3 is only calculated to be 156 m 2 g À1 .T he BET surface areas of CTF-HUST-A1-KOH, CTF-HUST-A1-EtOK, and CTF-HUST-A1-t BuOK are gradually increased to 210 m 2 g À1 ,4 12 m 2 g À1 ,a nd 644 m 2 g À1 .…”
Section: Resultsmentioning
confidence: 99%
“…Thereby,from the practical point of view,i ti sh ighly necessary to realize the direct photocatalytic overall water splitting for COFs in pure water, albeit it remains ag reat challenge. [7] Fori mproving the photocatalytic performance,t he crystallinity and hydrophilicity of the photocatalyst are reported to be the crucial factors.F or example,i mine-linked COFs based on sulfone unit have shown excellent photocatalytic hydrogen evolution performance due to the good hydrophilicity and crystallinity, [2b-f] whereas the study in hydrophilic CTFs is rarely demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25] Very recently,m edium-band gap conjugated polymers composedo fa lternating electron donor( D) and electron acceptor (A) have emerged as promising photocatalysts. [26][27][28][29][30][31][32][33][34][35][36] In contrastt og -C 3 N 4 and often used conjugated polymers formed by polymerization of same chemical units, such as polydopamine (PDA), [37][38] poly-3-hexylthiophene( P3HT), [39][40] polypyrrole (PPy), [41] and polyaniline (PANI), [42][43] the energyl evels of the D-A conjugated polymers can be facilely tuned by optimizing chemical structures of Do r Au nits for superior photocatalytic H 2 evolution rate (HER). [44][45] We previouslyc onstructed D-A conjugated based heterojunctions by in situ polycondensation and significantly enhanced their photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Constructing efficient bifunctional catalysts that can realize overall water splitting under visible‐light irradiation are of significant technical challenge due to the thermodynamical barrier in the overall water splitting . Until now, only few semiconductor photocatalysts for overall water splitting have been established . However, most of them exhibit a relatively low quantum efficiency due to their unsuitable band edge potentials for H 2 , O 2 evolution, or both.…”
Section: Introductionmentioning
confidence: 99%
“…However, as for a single photocatalyst, it is difficult to realize overall water splitting under visible‐light due to the incompatibility between narrow bandgap and strong redox ability. Meanwhile, the previous study indicates that building van der Waals heterostructures is advantageous to accelerate charge separation . Consequently, developing a direct Z‐scheme van der Waals heterojunction composed by two ultrathin nanosheets photocatalyst can tackle this issue due to the tunable band structures, suitable redox sites, the efficient charge transfer.…”
Section: Introductionmentioning
confidence: 99%